(3EKHGJ hLhO GdCfHjGA hGdChUjGA aj bHhQges - (3GdMSjfj GdcGXej, eMehO Hf aJM Gddg, b (B12 (3g`s ((3GdfLa GdCTQas)
(3ChdgG (B:s
(3GdMeO ddg (B... (3dG jHYO Yf CPgGf Phj GdYbhd aj GdEjeGf Gf QaYge Edi GdSeGA EfeG cGf deUdMI GbJVJgG GdMceI Ke Efge HYO Pdc QLYhG Edi GdCQV (B...s
(3BNQgG (B:s
...(3hRjGQI bHhQge hef Cf jbUOge ef HYO TbJge hHhf OhQge ajMQe GdGbJHGS ef QHGY RjGQJge hSGWY CfhGQges
(3JHUQI GdeDda (B:s
(3QHeG jchf (B: (3eMehO Hf GSeGYjd (B(2) (3Hf aJM Gddg Hf YGHO Hf dWa Gddg Hf eMeO eDef GdMSjfj, GdTjQGRj , JQLe GdRQcdj dGHfg MSf (B3/292s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B15 - 173 (1547)s
(3GdPQjYI (B15 - 173 (1547)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds